Impact of Pharmacists’ Intervention on the knowledge of HIV infected patients in a public sector hospital of KwaZulu-Natal - Saloshini Govender; Tonya Esterhuizen; Panjasaram Naidoo (African Journal of Primary Health Care & Family Medicine, 2011)
Background: The study site started its roll-out of the human immunodeficiency virus (HIV) prevention of mother-to-child transmission in 2006. All patients were counselled by trained counsellors, before seeing a doctor. At the pharmacy the medicines were collected with no intense counselling by a pharmacist as the patients would have visited the trained counsellors first. Subsequently it was found that there were many queries regarding HIV and acquired immune deficiency syndrome (AIDS). Thus a dedicated antiretroviral pharmacy managed by a pharmacist was established to support the counsellors. Objectives: The objective of the study was to assess the impact of a pharmacist intervention on the knowledge gained by HIV and AIDS patients with regard to the disease, antiretroviral drug use (i.e. how the medication is taken, its storage and the management of side effects) as well as adherence to treatment.